2015
DOI: 10.1016/j.enconman.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A eutectic mixture of galactitol and mannitol as a phase change material for latent heat storage

Abstract: a b s t r a c tThe thermophysical properties of mixtures of galactitol and mannitol were examined via differential scanning calorimetry (DSC) and X-ray powder diffraction (XRD) analysis. The aforementioned sugars were found to form a eutectic mixture at a 30:70 molar ratio of galactitol and manntitol, and displayed a melting point of 153°C while maintaining a high latent heat of fusion (DH fus = 292 J g À1 ). The XRD data revealed that the eutectic mixture contained the a, b, and d forms of mannitol with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…P. Hu declaimed that SAT containing 5 wt% AlN nanoparticles and 4 wt% CMC had no supercooling phenomenon while latent heat only decreased from 238.54 J g −1 to 227.54 J g −1 . However, another viewpoint maintained that the increased viscosity of system would restrict the diffusion of molecules from the melt to the nucleus, and thus resulted in the worsening of suppercooling and lowering speed of crystallization and heat transfer …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…P. Hu declaimed that SAT containing 5 wt% AlN nanoparticles and 4 wt% CMC had no supercooling phenomenon while latent heat only decreased from 238.54 J g −1 to 227.54 J g −1 . However, another viewpoint maintained that the increased viscosity of system would restrict the diffusion of molecules from the melt to the nucleus, and thus resulted in the worsening of suppercooling and lowering speed of crystallization and heat transfer …”
Section: Introductionmentioning
confidence: 82%
“…As an typical example, S. Zhang declared that well dispersed nanoparticles provided stable foreign nuclei to promote the heterogeneous nucleation and accelerate crystallization process. On the other hand, dynamic nucleation is another effective method to trigger crystallization because supercooling is also a kinetic controlled issue . Dynamic stimulation employs external stimuli, including mechanical vibration, stirring and ultrasonic irradiation, as supplementary energy to induce the nucleation of crystals .…”
Section: Introductionmentioning
confidence: 99%
“…They observed the same poor stability results than Solé et al [36] and concluded that this TES material is not suitable for the application proposed. Paul et al [38] studied the chemical stability of a eutectic mixture at a 30:70 molar ratio of galactitol and mannitol (T m = 153 ºC) via DSC, X-ray powder diffraction (XR) and FT-IR spectroscopy analyses. Those techniques confirmed that the combination of mannitol and galacticol showed good cyclic, thermal and chemical stability compared to its individual components under nitrogen or air atmospheres.…”
Section: Materials Requirements 21 Addressing Chemical Requirementsmentioning
confidence: 99%
“…When that occurs, PCM shows a significantly lower capacity to store heat [33]. According to [38] studied the effect of adding up to 0.5 wt.% of different nucleating agents (graphite and silver iodide) into an eutectic mixture at a 30:70 molar ratio of galactitol and mannitol (T m = 153 ºC).…”
Section: Materials Requirements 21 Addressing Chemical Requirementsmentioning
confidence: 99%
“…Moreover, the melting temperature can be adjusted to a suitable value by making a binary, trinary or even polynary eutectic in order to meet the practical applications. The paraffin and unitary, binary or even polynary fatty acids have well been studied as PCMs . However, as far as we know, the studies on fatty acid/n‐alkane mixture as PCMs is very few in the open literature.…”
Section: Introductionmentioning
confidence: 99%